Subthalamic deep brain stimulation aggravates speech problems in Parkinson's disease: Objective and subjective analysis of the influence of stimulation frequency and electrode contact location. (September 2019) - Phokaewvarangkul, Onanong; Boonpang, Kamolwan; Bhidayasiri, Roongroj
Abstract: Background: Speech disorders, including stuttering and hypophonia, have been reported in patients with Parkinson's disease (PD) after subthalamic deep brain stimulation (STN-DBS). Objective: To evaluate the effect of stimulation frequency or electrode contact location on speech disorders in PD patients with STN-DBS. Method: In this case-controlled study, we enrolled 50 PD patients with, and 100 PD patients without STN-DBS to compare their vocal intensities, measured by a sound pressure meter, and perceptual speech ratings, obtained from the speech sections of the United Parkinson's Disease Rating Scale (UPDRS) and subjective ratings regarding the impediment of functional communication by stuttering. For patients with STN-DBS, comparisons were made between high-frequency (HFS; 130 Hz), low-frequency (LFS; 80 Hz), and off-stimulation. We also evaluated the effect of electrode contact locations on speech function. Results: Patients with STN-DBS had decreased vocal intensities and UPDRS scores compared to those without ( p  < 0.05). Vocal intensity was significantly lower during HFS than during LFS and off-stimulation (both, p  < 0.05). Stuttering impeded STN-DBS patients' communication to greater extent than for those without (p  < 0.001). Vocal intensity was lower when active contacts were in the dorsal zone compared to those in the ventral zone ( p  < 0.05). Only STN-DBS treatment was a predictive factor for low vocal intensity (OR = 9.53, p  = 0.04). Conclusion: High-frequency STN-DBS with dorsal zone contacts can aggravate certain speech problems in PD patients. Therefore, it is important to balance between motor control and speech impairments in these patients. Highlights: Patients with Parkinson's disease exhibit speech disorders after STN-DBS. Stuttering impeded communication was greatest during HFS. Vocal intensity was lowest during HFS. Vocal intensity was lower when contacts were made in the active dorsal zone. STN-DBS was a predictive factor for low vocal intensity.